The Impact of Tourism on Uganda’s Economic Development: A Case Study of Lake Mburo National Park in Western Uganda - Joan Namugaanyi (Uganda Christian University, 2021)
This paper assesses the economic contributions of tourism at Lake Mburo National Park in Uganda through the analysis of the perceptions of the respondents on how tourism contributes to the local and national economies. From the survey responses, this research has identified three significant dimensions: entry fee collection, business income generation, and overall economic benefits from tourism activities. These findings reveal great appreciation for the potential of tourism to drive GDP and build national development; however, there is still much skepticism regarding whether tourism actually delivers in practical benefit to operators of tourism, accommodations, food, and beverages. The report also highlights various areas for improvement: revenue management, precise marketing techniques, and links to other sectors. Second, it requires the involvement of local communities to ensure transparency in the investment of tourism infrastructure for the impact to be economically realized. It is from this view that the study seeks actionable recommendations for stakeholders on ways through which sustainable tourism development can be fostered to benefit both the local community and the wider Ugandan economy